Penerapan Arsitektur Biophilic pada Pusat Kecantikan di Canggu: Bahasa Indonesia - Ni Putu Ayu Sri Wahyuni; I Wayan Widanan; I Ketut Sugihantara; Pande Putu Dwi Novigga Artha (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
A dynamic lifestyle and various daily routine activities, especially in urban areas, will gradually bring people to a point of saturation such as stress and depression. Therefore, everyone does various things to overcome the feeling of saturation point that they experience. What can be done to reduce the feeling of saturation point is to do me time. Me time can be done with various activities, one of which is carrying out comprehensive beauty treatments. The purpose of this research is to produce a design concept for a Beauty Center in which there are various comprehensive beauty treatments integrated within one site. The planning of this beauty center will apply the concept of biophilic architecture so that it can create a space in harmony with nature which can help the relaxation process. The methods used are literature studies, precedent studies, and field observations. The results of the research are the application of biophilic architecture to entrances, outdoor spaces, interior spaces and building facade.